Jawapan

2015-11-01T16:58:01+08:00
X +y = 5
x = 5 -y ................ P1

xy -2y = 2 ........... P2

gantikan P1 ke dalam P2;

xy -2y = 2
y(5 -y) -2y = 2
5y -y² -2y = 2
3y -y² = 2
y² -3y +2 =0
(y -2)(y -1) = 0

y -2 = 0
y = 2

y -1 = 0
y = 1

apabila y = 2, maka
x = 5 -y
x = 5 -2
x = 3

apabila y = 1, maka
x = 5 -y
x = 5 -1
x = 4
2015-11-02T12:25:31+08:00
X + y = 5
      y = 5 - x

subtitusikan (gantikan)
                     xy - 2y = 2
         x (5-x) - 2(5-x) = 2
       5x - x² - 10 + 2x = 2
-x² + 5x + 2x - 10 - 2 = 0
             -x² + 7x - 12 = 0
              x² - 7x + 12 = 0
              (x - 4)(x - 3) = 0
 
x - 4 = 0
    x₁ = 4
x - 3 = 0
    x₂ = 3